Single‐step purification of a small non‐mAb biologic by peptide‐ELP‐based affinity precipitation. Issue 12 (31st August 2020) - Mullerpatan, Akshat; Kane, Erin; Ghosh, Ronit; Nascimento, André; Andersen, Henrik; Cramer, Steven; Karande, Pankaj
Abstract: Affinity precipitation using stimulus‐responsive biopolymers such as elastin‐like polypeptides (ELPs) have been successfully employed for the purification of monoclonal antibodies. In the current work, we extend these studies to the development of an ELP‐peptide fusion for the affinity precipitation of the therapeutically relevant small non‐mAb biologic, AdP. A 12‐mer affinity peptide ligand (P10) was identified by a primary phage biopanning followed by a secondary in‐solution fluorescence polarization screen. Peptide P10 and AdP interacted with a K D of 19.5 µM. A fusion of P10 with ELP was then shown to be successful in selectively capturing the biologic from a crude mixture. While pH shifts alone were not sufficient for product elution, the use of pH in concert with fluid‐phase modifiers such as NaCl, arginine, or ethylene glycol was effective. In particular, the use of pH 8.5 and an arginine concentration of 500 mM enabled >80% product recovery. The overall process performance evaluated by sodium dodecyl sulfate‐polyacrylamide gel electrophoresis and reversed‐phase ultra‐performance liquid chromatography analyses indicated successful single‐step purification of the biologic from an Escherichia coli lysate resulting in ∼90% purity and >80% recovery. These results demonstrate that phage display can be readily employed to identify a peptide ligand capable of successfully carrying out the purification of a non‐antibody biological product using ELP‐based affinity precipitation. Abstract :